Decentralized Control of Voltage- And Current-Controlled Converters Based on AC Bus Signaling for Autonomous Microgrids - De Araujo, Lucas Savoi; Alonso, Augusto M. Dos Santos [UNESP]; Brandao, Danilo Iglesias (Institute of Electrical and Electronics Engineers (IEEE), 2020)
This article proposes a fully decentralized control approach, based on AC bus signaling, to integrate the operation of voltage- and current-controlled converters that exist in an isolated low-voltage microgrid, so they may be fully steered under grid-feeding, grid-supporting, and grid-forming control principles. The proposed strategy, devised by classic and modified droop-based controllers, allows control of the microgrid active power relating to the system frequency, while regulating the reactive power related to the voltage, dispensing any need for communication infrastructures. Beyond ensuring proper microgrid power balance at all times, the control strategy prioritizes energy extraction from non-dispatchable sources (i.e., photovoltaic-based systems), whereas it uses dispatchable sources (i.e., battery-based systems) to share active and reactive power proportionally to their capabilities. As a consequence of the proper and novel management of battery-based converters, battery overvoltage and overcurrent are avoided, supporting a prolonged lifespan. Simulation results considering an autonomous microgrid operating under several scenarios are presented, to demonstrate the capabilities of the proposed control scheme on steering the different topologies of converters.
Keywords: Battery energy storage systems; decentralized control; distributed generation; microgrids; power control